The Link Between Employees’ Organizational Tenure and Citizenship Behaviour: do Different Types of Trust Play Important Role? - Bee Seok, Chua; Adela Mutang, Jasmine; Hudani Md. Nawi, Nurul; Wider, Walton; Cho Chiew, Tan (International Journal of Engineering and Technology, 2018)
This study aims to examine the mediating effects of five different types of employees’ trust on the relationship between employees’ organizational tenure and their organizational citizenship behaviour. Using data obtained from 163 employees from banking organization located in Kota Kinabalu, Sabah. Structural equation modelling was used to assess the relationship between variables. The Employees Trust Scale and Organizational Citizenship Behaviour Scale were used to measure the variable. The relationship between the variables was analysed by using partial least squares structural equation modelling [PLS-SEM]. Results showed that the direct effect of employee organizational tenure showed a positive but not significant effect towards organizational citizenship behaviour. For the direct effect of employee’s trust towards their organizational citizenship behaviour, the sub scale of integrity and relationship influence organizational citizenship behaviour significantly. The sub scale of integrity shows a negative and significant effect towards organization citizenship, whereas the sub scale of relationship affects organizational citizenship behaviour positively. While, the mediation test showed mediation effect did not exist between employee organizational tenure, employee’s trust, and organizational citizenship behaviour. The final part of analysis indicated the model has adequate predictive relevance.